Linguistic features in the introduction section of the hospitality and management research articles - John Philip De Mello, Geraldine; Rafik-Galea, Shameem; Chan, Swee Heng; Arumugam, Nalini (Malaysian Association of Modern Languages, 2015)
This paper reports a corpus-based genre analysis of the use of linguistic features in the introduction section of Hospitality and Management research articles (HM RAs). It explores the frequently used linguistic features such as modal verbs, personal pronouns, demonstrative pronouns, tenses, conjuncts, hedging, citations- integral and non-integral and the use of questions. The samples used were 20 RAs taken from the Journal of Hospitality and Management and published between the years 2004 - 2006. The linguistic features of the introduction section were identified using the Wordsmith program (Scott, 1998) and manually recording and counting the frequency of occurrence in each move. It is noted that the modals ‘can’ and ‘may’ are used simultaneously in all the three moves identified in the HM RA introductions. Interestingly, the analysis of the linguistic features in the present study shows that it is necessary for the HM RA writers to use different linguistic features while discussing certain moves such as the use of the present tense, which is predominant in Move 1, Move 2 and Move 3 while the present perfect and past tense are found in Move 1 and 3. The study indicates that identification of the linguistic features in the introduction section of the HM RAs may be helpful for students and novice writers in the field because they may be able to use these features as an initial suggested list of choices that they can effectively use in their writing.